1777 N.C. Sess. Laws 41, 43-44 - (:unkn) unknown (My University, 1777)
Ch. 6, § 9: That all persons failing or refusing to take the Oath of Allegiance, and permitted by the County Courts, as immediately aforesaid, to remain in the State, shall be adjudged incapable and disabled in Law to have, occupy or enjoy, any Office, Appointment, License, or Election of Trust or Profit, civil or military, within this State, and shall not be capable of being elected to, or aiding by their Votes to elect another to be a Member of Assembly, and shall not by themselves, or by Deputy, Attorney or Trustee, execute any such Office, Trust or Appointment, and shall be disabled to prosecute any Suit at Law or Equity, or to be Guardians, Executors or Administrators, or capable of any Legacy, or Deed of Gift of Lands, and shall be disabled from taking any Lands by Descent or Purchase, or conveying Lands to others for any Term longer than for one Year, and shall not keep Guns or other Arms within his or their House, but the same may be seized by a written Order of a Justice of the County in which he or they reside; and after the Expiration of the said Sixty Days, he or they shall not be permitted to depart this State without Permission first had and obtained from the Governor and Council; and in Case of being suffered to depart, shall give Bond and sufficient Security, if such shall be required, not to be aiding to the Enemies of this State during his or their Absence; and in Case of their Departure without such Permission had, he or they shall forfeit all their Goods and Chattels, Lands and Tenements, to the Use of the state?"
Keywords: POSSESSION - DANGEROUS PERSONS; LOYALTY OATH REQUIRED